An optimized eDNA protocol for fish tracking in estuarine environments - Fouad El Baidouri; Alison W. Watts; Jeffrey T. Miller; Muriel Kelly; Joseph L. Sevigny; Heather Gilbert; W. Kelley Thomas (Scientific Reports)
Abstract Environmental DNA (eDNA) is revolutionizing how we investigate biodiversity in aquatic and terrestrial environments. It is increasingly used for detecting rare and invasive species, assessing biodiversity loss and monitoring fish communities, as it is considered a cost-effective and noninvasive approach. Some environments, however, can be challenging for eDNA analyses. Estuarine systems are highly productive, complex environments, but samples collected from these settings may exhibit PCR inhibition and a low fish read recovery. Here we present an approach for detecting fish in turbid, highly productive estuarine systems. The workflow includes bead-based extraction, inhibition removal, high fidelity and specificity DNA polymerase (Platinum SuperFi II) and multiplexing the universal MiFish primers. By applying this hybrid method to a variety of complex estuarine samples with known inhibition, we have more than doubled the number of recovered fish species while removing most of the off-target amplification.